2003
DOI: 10.1046/j.1467-789x.2003.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

How much physical activity is enough to prevent unhealthy weight gain? Outcome of the IASO 1st Stock Conference and consensus statement

Abstract: A consensus meeting was held in Bangkok, 21-23 May 2002, where experts and young scientists in the field of physical activity, energy expenditure and body-weight regulation discussed the different aspects of physical activity in relation to the emerging problem of obesity worldwide. The following consensus statement was accepted unanimously. 'The current physical activity guideline for adults of 30 minutes of moderate intensity activity daily, preferably all days of the week, is of importance for limiting heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
436
4
45

Year Published

2005
2005
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 708 publications
(516 citation statements)
references
References 74 publications
31
436
4
45
Order By: Relevance
“…We found larger summary effects after pooling studies which prescribed a higher vs lower dose of exercise (155-180 vs 120-150 min/weeks), and in those pooled after removing studies which did not report exercise compliance or change in physical activity levels. However, current recommended doses (volumes) of exercise/physical activity for treating overweight in children and adolescents published by several expert committees (B30-60 min/days at moderate intensity, most days (210-360 min/weeks)) 73,74 as well as USDA's Dietary Guidelines for Americans 2005, 75 are substantially higher than doses which have been tested in RCTs in young overweight cohorts, to date. In fact, we found no randomized trial in the English published literature to have prescribed a dose of more than 200 min/weeks of aerobic exercise to overweight children.…”
Section: Discussionmentioning
confidence: 99%
“…We found larger summary effects after pooling studies which prescribed a higher vs lower dose of exercise (155-180 vs 120-150 min/weeks), and in those pooled after removing studies which did not report exercise compliance or change in physical activity levels. However, current recommended doses (volumes) of exercise/physical activity for treating overweight in children and adolescents published by several expert committees (B30-60 min/days at moderate intensity, most days (210-360 min/weeks)) 73,74 as well as USDA's Dietary Guidelines for Americans 2005, 75 are substantially higher than doses which have been tested in RCTs in young overweight cohorts, to date. In fact, we found no randomized trial in the English published literature to have prescribed a dose of more than 200 min/weeks of aerobic exercise to overweight children.…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, a consensus meeting concluded that 45-60 min a day of moderate PA per day was required to prevent the transition to overweight or obesity, 38 substantially more than the 1995 recommendation that every adult should accumulate 30 min or more of moderate-intensity PA on most, preferably all, days of the week. 30 Future prospective studies incorporating pedometer or accelerometer measures of activity should assist the evidence base for future recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…18 Our activity measures in adulthood provide a measure of frequency, not duration or intensity, but all three aspects of activity have been found to be relevant to body fatness or weight maintenance. 19,20 Indeed, current physical activity recommendations are based on all three aspects, stating that 30 min of moderate activity should be accumulated on at least 5, but preferably all days of the week. A major strength of the 1958 cohort is that, unlike many studies, it has measures at several ages and over a long time period.…”
Section: Discussionmentioning
confidence: 99%